PROSPECTIVE DIRECTIONS OF INTRODUCTION OF INNOVATIVE TECHNOLOGIES IN TOURISM - Asilbek Xudoyberdiev (Journal of new century innovations, 2022)
Annotation: This scientific article highlights the current state of tourism, which has become one of the most lucrative businesses in the world today. It has become an integral part of a market economy and has become a rapidly growing industry in many countries of the world. Tourism is developing in close cooperation with the world's transport, communications, trade, construction, agriculture and consumer goods industries, and is gaining a foothold in the global economy.